Provision of FE Tablets to The Event of Anemia in Adolescent Women in The Area Community Health Center Technical Implementation Unit Liggang Bigung - Latif, Nursyani; Mardiana, Nina; Rahman, Gajali (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Adolescent girls will experience menstruation every month which at this time of menstruation they will be at risk of developing anemia. The impact of iron deficiency anemia includes lack of concentration in school-age adolescents which results in decreased school achievement, decreased work ability for workers so that their productivity is reduced. Objective: The purpose of this study was to see the effectiveness of giving Fe tablets to the incidence of anemia. Methods: Using a pre-experimental research design with control. The population in the study was 97 young women at Junior High School 01 Linggang Begung. Results: the results of the Wiloxcon test in the intervention group were obtained (p value 0.000<?<0.05). These results explain that there is a significant effect of the intervention on Hb levels with (p value < = 0.05). These results explain that there are differences in the intervention of Hb levels in the intervention and control groups with (p value < = 0.05). Discussion: Administration of Fe tablets can increase the erythropoiesis process which initiates the formation of mitotic unipotential stem cells while differentiation into erythrocyte cells when stimulated by erythropoietin also stimulates further mitosis of promonoblasts, basophilic normoblasts and polychromatophilic normoblasts. Conclusion: there was an increase of 1.95 g/dl in the intervention group and 0.15 g/dl in the control group. Where the administration of Fe tablets with a commitment to consuming Fe tablets can increase Hb levels for 1 month of administration